Associations Between the Cyclic Guanosine Monophosphate Pathway and Cardiovascular Risk Factors: MESA - Ying, Wendy (J Am Heart Assoc, 2019)
BACKGROUND: cGMP mediates numerous cardioprotective functions and is a potential therapeutic target for cardiovascular disease. Preclinical studies suggest that plasma cGMP is reflective of natriuretic peptide stimulation. Epidemiologic associations between cGMP and natriuretic peptide, as well as cardiovascular disease risk factors, are unknown. METHODS AND RESULTS: We measured plasma cGMP in 542 men and 496 women free of cardiovascular disease and heart failure in MESA (Multi‐Ethnic Study of Atherosclerosis). Cross‐sectional associations of N‐terminal pro‐B type natriuretic peptide, sex hormones, and cardiovascular disease/heart failure risk factors with log(cGMP) were analyzed using multivariable linear regression models. Mean (SD) cGMP was 4.7 (2.6) pmol/mL, with no difference between the sexes. After adjusting for cardiovascular risk factors, N‐terminal pro‐B type natriuretic peptide was significantly positively associated with cGMP (P<0.05). Higher blood pressure and lower estimated glomerular filtration rate were associated with higher cGMP (P<0.05). Triglyceride levels, total/high‐density lipoprotein cholesterol ratio, presence of diabetes mellitus, and the homeostatic model assessment of insulin resistance were inversely associated with cGMP (P<0.05). Among women, free testosterone and dehydroepiandrosterone were inversely associated with cGMP, while sex hormone binding globulin was positively associated (P<0.05). CONCLUSIONS: In a community‐cohort, plasma cGMP was associated with natriuretic peptide signaling. Higher blood pressure and greater renal dysfunction were positively associated with cGMP, while adverse metabolic risk factors were inversely associated. Increased androgenicity in postmenopausal women was inversely associated with cGMP. These novel associations further our understanding of the role of cGMP in a general population.